(untitled) (Journal of Medical & Health Sciences Review, 2025)
Cancer is still a huge problem because of the complication of genetic heterogeneity and emergence of drug resistance which leads to poor therapeutic responses. Conventional drug development is usually restricted in their capacity to discover the exact molecular target and anticipate the drug responses. This is because the integration of CRISPR-based genome editing technologies into cancer drug screening does two main services: it offers a new direction of discovering gene-drug interactions and targeting against drugs. The study has used A549, MCF-7, and HCT116 cancer cell lines to examine how the consequences of knocking out and activating certain genes (KRAS, TP53, MYC, PTEN, and EGFR) affect a cell in terms of response to chemotherapeutic agents ( d o x rubicin, paclitaxel and c is platinum ). The design of the experiment was the inclusion of drug treatments at different concentrations, cell viability assays, measurement of gene expression and quantifying the protein. The statistical tests, such as ANOVA and post-hoc testing, were used in order to determine the statistical significance of the changes. The data showed that KRAS knockout sensitized the A549 cells to doxorubicin (IC50 = 0.35 10 9 ) and TP53 knockout rendered the cells resistant (IC50 = 1.50 10 9 ). MYC CRISPR interference decreased sensitivity to paclitaxel whereas MYC activation increased it. PTEN knockout (in MCF- 7) rendered cells more susceptible to cisplatin and activation induced resistance. Pearson correlation analysis demonstrated that there were significant correlations between the change in expression of the genes and cell viability indicating the functional relevance of the CRISPR alterations. The presented study also notes that CRISPR-based functional screening can be a promising field of precision oncology and can help to understand the molecular underpinning of drug resistance and discover new targets of therapeutics against cancer